High-value utilisation of ceramic waste powder in PVC-based composite and basalt fibre reinforcement effect on its performance. Issue 13 (1st July 2022) - Li, Yi; Ding, Chong; Zhang, Na; Wang, Qi; Zhang, Youpeng; Di, Xiangyun; Zhang, Yihe
Abstract: Herein, ceramic waste (CW) powder and basalt fibre (BF) were used as inorganic filler and reinforcement, respectively, to prepare polyvinyl chloride (PVC)-based composites. The influence of the CW content on the rheological and mechanical properties of PVC-based composites was studied to attain a proper CW filling content. Besides, the effects of BF addition on the mechanical properties, water resistance, thermal conductivity and thermal stability of the BF/CW/PVC composites were investigated. The results show that although plasticising time is prolonged as the CW filling content increases, the CW/PVC composites still have good processability under high-filling content of 50 wt% CW. The addition of 10 wt% BF improves the mechanical properties of the CW/PVC composite. The BF/CW/PVC composites have good water resistance and thermal insulation performances. The CW filling powder and BF significantly improve the thermal stability and enhance the deformation resistance and storage modulus of the composites. This work provides a high-value utilisation method for recycling CW.